A Curious Case of Hyperpigmented Macules with Inducible Wheals - Shreya Deoghare; Ajay Kumar; Devayani Pol; Mahendra Singh Deora (Wolters Kluwer Medknow Publications, 2023)
Abstract A provisional diagnosis of urticaria pigmentosa was revised to lichen planus pigmentosus with dermatographism, after histopathologic examination of specimen from hyperpigmented patch. It is important to keep differential diagnosis of inducible wheals while making a diagnosis.